Diagnostic performance of P wave duration in the identification of left atrial enlargement in dogs - Savarino, P.; Borgarelli, Michele; Tarducci, A.; Crosara, S.; Bello, Nora M.; Mariocco, M. L. (My University, 2012)
Objectives: To determine sensitivity and specificity of P wave duration in the identification of left atrial enlargement (LAE) in dogs. Methods: Electrocardiograms (ECG) from normal dogs and dogs with various cardiovascular diseases were evaluated. Inclusion criteria were the availability of an ECG showing a stable isoelectric line, easily recognizable P waves and good quality 2D echocardiographic estimate of left atrial dimensions using the left atrial to aortic root ratio (LA/Ao). Using a metal caliper system, P wave duration was measured to the nearest 10 msec for six consecutive heart beats; data were then averaged for each dog. The accuracy of P wave duration in predicting LAE was determined using a Receiver Operating Characteristic (ROC) analysis. Results: 156 dogs were included in the study. Average P wave durations of 20, 30, 40 and 50 msec yielded sensitivities of 100%, 85%, 68% and 40% and specificities of 0%, 16.04%, 64.15% and 93.4%, respectively, for the diagnosis of LAE by echocardiography. The estimated Area Under Curve (AUC) of the ROC curve was 0.70 (95% confidence interval: 0.60-0.80). Clinical significance: The diagnostic performance of P wave duration for identification of LAE in dogs presents considerable limitations.
Keywords: P wave; Dog; Left atrial enlargement